Longitudinal accuracy analysis of ultrasound performed during a four‐year emergency medicine residency. Issue 3 (17th February 2021) - Schleifer, Jessica; Haney, Rachel M.; Shokoohi, Hamid; Huang, Calvin K.; Ratanski, Daniel; Kimberly, Heidi; Liteplo, Andrew S.
Abstract: Background: The objective of this study was to analyze patterns of point‐of‐care ultrasound (POCUS) performance over 4 years of emergency medicine (EM) residency. Specifically, we aimed to study how accuracy and adherence to standards of scanning changed by postgraduate year (PGY). Methods: This was a retrospective observational study of resident‐performed POCUS at an academic emergency department over 6 years. We reviewed records of POCUS scans performed by PGY‐1 to ‐4 residents that had been collected for quality assurance purposes. Data that were collected about EM residents' performance included the total number and type of scans per year, rate of technically limited scans (TLS), and accuracy on interpreting ultrasound images. Resident performances in each year (PGY‐1 to ‐4) were independently evaluated and reported. Results: During a 6‐year period, 137 different EM residents performed 50, 815 ultrasound scans. The median number of scans was 177 for PGY‐1, 124 for PGY‐2, 118 for PGY‐3, and 76 for residents in PGY‐4. The accuracy of scan interpretations were high across all PGY levels (>97%), but slight degradation was observed as residents progressed through residency. The TLS rate increased from 4.7% among PGY‐1s to 13.6% as PGY‐4s. Conclusions: In this large cohort of POCUS studies by EM residents, POCUS accuracy rates decreased and rates of TLS significantly increased as residents progressed through residency.